Learning from Presidential Debates: Who Learns the Most and Why?. Issue 5 (19th October 2020) - Jennings, Freddie J.; Warner, Benjamin R.; McKinney, Mitchell S.; Kearney, Cassandra C.; Funk, Michelle E.; Bramlett, Josh C.
ABSTRACT: Perhaps one of the most well-established findings stemming from decades of research exploring the effects of televised presidential debates is that exposure to this "information-rich" source of campaign communication enables viewers' acquisition of issue knowledge. However, certain individuals will benefit more from the debate viewing experience because differences in individual characteristics allow some to learn more than others. In this quasi-experimental study, we test whether those with more pre-debate knowledge, political information efficacy, and need for cognition gain more information from debate viewing. In so doing, we clarify the mechanisms that underlie information acquisition from debates and consider the boundary conditions that constrain debate learning. The findings provide more nuance to our understanding of the mechanisms behind the learning of political knowledge from televised candidate debates. Abstract :